Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Nasabah Taplus Muda PT. Bank Negara Indonesia (Persero) Tbk. Kantor Cabang Manado - Bayuningsih, Effie Nurita (Universitas Sam Ratulangi, 2018)
The purpose of this study is to analyze the simultanously influence of service quality and brand image toward Taplus Muda’s customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang Manado. Analyze the influence of service quality toward Taplus Muda’s customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang Manado. Analyze the influence of brand image toward Taplus Muda’s customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang Manado. This type of research is a kind of research associative by using data analysis technique that is regression analysis. The result of the research show that (1) service quality and brand image to simultanously had influence on customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang Manado (2) service quality has influence on customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang Manado (3) brand image has influence on customer satisfaction of PT. BNI (Persero) Tbk. Kantor Cabang ManadoKeywords: Service Quality, Brand Image, Customer Satisfaction, BNI